PENETAPAN ‘ADAM WALI NIKAH OLEH PEJABAT KUA DI KOTA SEMARANG - Rokhmadi, Rokhmadi (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2016)
This article is result of the study that describes the determination concept of adam wali nikah by officials of the Religious Affairs Office (KUA) in Semarang, on marriage guardian of an ineligible woman, that because of the bride’s birth is less than six months from her parents’ marriage. Having determined adam marriage guardians’ status, then KUA establishes that the marriage guardian is delegated to KUA officials in each region of Semarang. As for the basis used by those who determine the delegation for the reason of deficient condition of marriage guardians for a female to the KUA is the use of the legal basis contained in adam marriage guardians’ determination in the letter of Director General Guidance and Pilgrimage Affairs Number: D/ED/PW.01/03/1992, in which its position is under the Marriage Legislation No. 1 of 1974 and the Islamic Law Compilation (KHI).